Neurocognitive Functioning In Ketum (Mitragyna Speciosa Korth) Leaf Users In Northern Parts Of Peninsular Malaysia - Alamdari, Solmaz Azimi (2012)
Abuse of ketum (Mitragyna speciosa Korth) has increased recently in Malaysia. While there are extensive pharmacological studies of ketum effects on animals, human studies on patterns of neuropsychological function of ketum leaf users are limited. To measure the neurocognitive function of ketum users in the northern parts of peninsular Malaysia and compare it with that of healthy non-drug users (control group) and heroin dependents, also to compare the neurocognitive function of long term and short term ketum users.